Theoretical and legal aspects of the reform of the system of administrative services in Kiev - Кохан, Богдан Андрійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The article discusses the theoretical foundations-legal reforming the system of administrative services, useful innovations, problems arising from the reform of the system of administrative services in Kiev. Also, it states on ways to optimize the practical implementation of the provision of administrative services. And the service is considered an ideology, as a theoretical basis of administrative services. Analysis of the subject of reforming the system of administrative services in the Kiev is critical, because right now there are changes in the Ukrainian state, which can be described as a transition from the forms of management powers to the service. Consideration of this subject is an example of Kiev, because the capital is rapidly reforming the system of administrative services. Problems concerning the provision of administrative services actively considered Ukrainian scientific opinion on the Constitution of Ukraine on June 28, 1996. In Ukraine, in recent years, are increasingly term "administrative services" because the category of "administrative services" currently has more substantial burden in economic sciences. Recently, much was made of normative legal and institutional measures to reform the system of administrative services. It should be noted that changes in the system contributed to facilitating citizens’ access to administrative services and the convenience of receiving them. The main focus of reforming the system of administrative services in the Kiev has become their availability to the public, as well as quality service ЦНАП that does not always correspond to the declared standards. Understanding and application service ideas based on the development system is an important factor for the further development of the system of administrative services. Administrative services, as well as any services in the private sphere should meet the challenges of our time and be of high quality (provided in the terms and amount claimed for the particular services). If the impetus for the evolution and improvement of services in the private sphere is their competitiveness in the market, in the case of administrative services, which result from the exercise of authority is not a factor of market competition that encourages development. Thus the quality of administrative services depends on the decisions of individuals who have authority and of public control.